Laura Gilpin: An enduring grace - Sandweiss, Martha A. (Amon Carter Museum Fort Worth, TX, 1986)
This is the first book devoted to the life and work of one of America's finest photographers, Laura Gilpin (1891-1979). Ms. Gilpin photographed the American Southwest for more than sixty years, creating an extraordinary document of the land its people. She is best known for her photographs of the Pueblo and Navajo Indians that constitute a major contribution to the documentation of Southwestern Indian life, bridging the gap between the studied sentimentality of earlier Indian photography and the objective documentation of later work.
56194
Keywords: Laura Gilpin -- Biography -- Exhibitions -- Plates (photography) -- United States; Photography -- Southwest; Pueblo Indians -- Photography; Navajo Indians -- Photography